METHODOLOGICAL FEATURES OF TEACHING MATHEMATICS IN PRIMARY SCHOOL ACCORDING TO THE PROGRAM OF THE NEW UKRAINIAN SCHOOL - Сяська, Наталія (SWorldJournal, 2024)
Distance learning and martial law have had a negative impact on the quality of mathematics education, as well as on education reform in general. This article discusses the methodological features of teaching mathematics in primary school and ways to impro